The Developmental Puzzle of Irony Understanding: Is Epistemic Vigilance the Missing Piece? - Milosavljevic, Ana; Castelain, Thomas; Pouscoulous, Nausicaa; Mazzarella, Diana (Journal of Child Language, 2026)
The prolonged developmental window of irony understanding opens up the question of which socio-cognitive repertoire underlies this pragmatic capacity. In the present study, we investigated the relationship between epistemic vigilance and irony understanding in 5/6- and 6/7-year-old children using a picture selection task. We assessed children's vigilance towards unreliable informants and manipulated the reliability of the irony target. Our findings confirm that irony comprehension is a late-emerging skill and highlight the need to differentiate its full-fledged understanding from mere sensitivity to contextual mismatches. While irony understanding was not affected by our reliability manipulation, our findings revealed that more vigilant children were better at irony understanding than less vigilant ones. This provides the first empirical evidence that epistemic vigilance is a good predictor of irony performance and lays the ground for future research on the intricate relationship between these two capacities.